2007
DOI: 10.1002/jcb.21359
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that PI3K, Rac, Rho, and Rho kinase are involved in basic fibroblast growth factor‐stimulated fibroblast–Collagen matrix contraction

Abstract: Fibroblast-collagen matrix contraction has been used as a model system to study how cells organize connective tissue. Previous work showed that lysophosphatidic acid (LPA)-stimulated floating collagen matrix contraction is independent of Rho kinase while platelet-derived growth factor (PDGF)-stimulated contraction is Rho kinase-dependent. The current studies were carried out to determine the signaling mechanisms of basic fibroblast growth factor (bFGF)-stimulated fibroblast-collagen matrix contraction. Both bF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…The ERK and PI3-kinase/Akt signaling pathways are known to be involved in keratinocyte migration [21], [22]. Therefore, we next investigated the involvement of ERK and PI3-kinase/Akt signaling pathways in VPA-induced keratinocyte migration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ERK and PI3-kinase/Akt signaling pathways are known to be involved in keratinocyte migration [21], [22]. Therefore, we next investigated the involvement of ERK and PI3-kinase/Akt signaling pathways in VPA-induced keratinocyte migration.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, these two pathways are crucial for cutaneous wound healing [6], [7]. Growth factors such as epidermal growth factor (EGF) and basic fibroblast growth factor (bFGF) accelerate keratinocyte migration and epithelialization in skin wound healing by activating the ERK and PI3-kinase/Akt signaling pathways [21], [22]. Conversely, inhibition of these signaling pathways has been shown to impair corneal wound healing [23].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the reduced contractility of the Ext1 Gt/Gt fibroblasts observed in the present study may rely on a reduced signaling response to FGF2; however, this remains to be confirmed. FGF2-induced contraction of floating collagen lattices was previously shown to involve phosphatidylinositol 3-kinase, Rac, Rho, and also Rho kinase (41), implying that the intracel- lular signaling mechanisms that drive collagen gel contraction are complex and that several different signaling pathways act in parallel. HS binds to collagen I via a single binding site near the NH 2 terminus on the collagen monomer (42).…”
Section: Figure 7 Ext1mentioning
confidence: 99%
“…Lakshman et al (16) demonstrated a role for Rho kinase (ROCK) in matrix remodeling by corneal fibroblasts. Abe et al (1) showed that activation of Rho and ROCK are required for increased collagen gel contraction by dermal fibroblasts in response to basic FGF. Importantly, Shimizu et al (31) reported that Rho and its target ROCK contribute to lung fibrosis in the bleomycin mouse model and that a selective ROCK inhibitor can prevent development of fibrosis in this model.…”
Section: Discussionmentioning
confidence: 99%